Finite-difference methods for solving loaded parabolic equations - Abdullayev, V. M.; Aida-zade, K. R. (Computational mathematics and mathematical physics, 2016)
Loaded partial differential equations are solved numerically. For illustrative purposes, a boundary value problem for a parabolic equation with various point loads is considered. By applying difference approximations, the problems are reduced to systems of algebraic equations of special structure, which are solved using a parametric representation involving solutions of auxiliary linear systems with tridiagonal matrices. Numerical results are presented and analyzed.